Learning everyday entrepreneurial practices through coworking. Issue 3 (July 2018) - Butcher, Tim
This article aims to understand learning in coworking. Coworking is an emergent global phenomenon that involves independent workers, often from various occupational backgrounds, working collectively in shared workspaces. I situate coworking in broader debates on entrepreneurialism and socioeconomic change to conceptualise it as a twofold process: of learning everyday coworking practices and learning through coworking practices. While coworking, individuals learn to make sense of their place in the entrepreneurial milieu by developing practices that contest established entrepreneurial norms. Drawing on an ethnographic study, I show how coworkers learn to become collaborative, intentional and to perform contestation through co-created situated learning. That learning enables them to co-construct a sense of community necessary to become entrepreneurially proficient in an increasingly uncertain world of work. By critically understanding why and how learning occurs in coworking, this research contributes to our knowledge of what learning is, and why and where it can occur.